2014
DOI: 10.1371/journal.pone.0103440
|View full text |Cite|
|
Sign up to set email alerts
|

Roles of PI3K/Akt and c-Jun Signaling Pathways in Human Papillomavirus Type 16 Oncoprotein-Induced HIF-1α, VEGF, and IL-8 Expression and In Vitro Angiogenesis in Non-Small Cell Lung Cancer Cells

Abstract: Background and ObjectivesHuman papillomavirus (HPV)-16 infection may be related to non-smoking associated lung cancer. Our previous studies have found that HPV-16 oncoproteins promoted angiogenesis via enhancing hypoxia-inducible factor-1α (HIF-1α), vascular endothelial growth factor (VEGF), and interleukin-8 (IL-8) expression in non-small cell lung cancer (NSCLC) cells. In this study, we further investigated the roles of PI3K/Akt and c-Jun signaling pathways in it.MethodsHuman NSCLC cell lines, A549 and NCI-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
93
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 43 publications
1
93
0
Order By: Relevance
“…LMO4 can inhibit the expression of the fusion proteinengrailed-LMO4 while suppressing cell growth, and can induce the apoptosis of breast cancer cells, indicating that LMO4 contributes to oncogenesis by similar mechanisms, thus enhancing cell survival and proliferation (19). AKT/PI3K activation is involved in the carcinogenesis and tumor progression of various solid tumors, including NSCLC (20,21). Lu et al reported that the transcriptional coactivator LMO4 modulated the cytostatic effects of TGF-beta in epithelial cells, and associated with and regulated a prototype Smad target promoter (14).…”
Section: Discussionmentioning
confidence: 99%
“…LMO4 can inhibit the expression of the fusion proteinengrailed-LMO4 while suppressing cell growth, and can induce the apoptosis of breast cancer cells, indicating that LMO4 contributes to oncogenesis by similar mechanisms, thus enhancing cell survival and proliferation (19). AKT/PI3K activation is involved in the carcinogenesis and tumor progression of various solid tumors, including NSCLC (20,21). Lu et al reported that the transcriptional coactivator LMO4 modulated the cytostatic effects of TGF-beta in epithelial cells, and associated with and regulated a prototype Smad target promoter (14).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence revealed that the PI3K/Akt pathway is activated in multiple types of cancer, including kidney, lung, liver and ovarian cancer, and has an important role in migration and invasion (26)(27)(28). Several studies reported that the PI3K/Akt pathway is mediated by the SHH pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that PDGF is crucial for pulmonary vascular remodeling [16]. PDGF-mediated PAH involves multiple mechanisms, including the ERKl/2and PI3k/Akt signaling pathways [23, 24], both of which ultimately results in an over-expression of VEGF [25, 26]. Moreover, recent reports have revealed that tumor angiogenesis is driven by a complex interplay between the pro-angiogenic VEGF/ VEGFR and PDGF/PDGFR pathways within the tumor microenvironment [27].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, KLF4 promotes angiogenesis by activating VEGF signaling in endothelial cells [25, 26]. The Krüppel-like family is a group of transcription factors characterized by the presence of a three-zinc finger DNA-binding domain.…”
Section: Introductionmentioning
confidence: 99%